BaGa4O7, a new A3BC10O20 crystalline phase: synthesis, structural determination and luminescence properties1. Issue 32 (28th August 2015) - Boyer, Marina; Véron, Emmanuel; Becerro, Ana Isabel; Porcher, Florence; Suchomel, Matthew R.; Matzen, Guy; Allix, Mathieu
<x xml:space="preserve">Abstract</x> A new compound, BaGa4O7, is found by cooling from the melt. Part of the A3BC10O20 family, it exhibits strong orange-red luminescence emission when doped with Eu3+.